4. CHARACTERISTICS OF CHILDREN WITH ACYANOTIC CONGENITAL HEART DISEASE WITH LEFT TO RIGHT SHUNT AT CHILDREN'S HOSPITAL 2 FROM JANUARY 1, 2024 TO DECEMBER 31,2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine epidemiological, clinical, paraclinical and treatment characteristics of children with acyanotic congenital heart disease with left-right shunt at Children's Hospital 2 from January 1, 2024 to December 31, 2024Method: Description of case series.Results: There were 540 cases in the study, the proportion of females was 53.3%. The average age in months was 11 ± 41.1. The age group 1 -
Keywords: Congenital heart diseases, Children’s Hospital 2.